Physical and fruit region characterization of araticum and seed germination as a result of accesses - Costa da Silva, Edvan; Villa, Fabíola; Fernandes da Silva, Daniel; Possenti, Jean Carlo; Sabini da Silva, Luciana; Eberling, Tatiane (Comunicata Scientiae, 2022)
The physical characteristics of the fruits are of great importance for the identification and selection of superior genetic materials, appropriate for commercialization or industrial use. Given the above, the objective was to physically characterize the araticum fruit and to verify the influence of accessions and fruit region under seed germination. The work was developed at Unioeste, Marechal Cândido Rondon Campus (PR), and conducted at the University Laboratory of Post-Harvest Technology. Ripe fruits of araticum (Annona sylvatica) were collected from four native plants (accessions A1, A 2, A3, and A4) at the Experimental Farm of the University in February 2019. As for the physical evaluation of the fruits, four repetitions of 10 randomly chosen ripe fruits per access were evaluated. The longitudinal diameter, transversal diameter, fruit biomass, epicarp biomass, fruit pulp, number of seeds, and mass of 100 seeds were the characteristics evaluated. The experimental design used for the germination test was completely randomized, in a factorial scheme 4 x 2 [4 accessions (A1, A2, A3, and A4) x 2 regions of the fruit (proximal and distal) in 500 mg L-1 of acid gibberellic (GA3)], containing 4 repetitions and 25 seeds per repetition. The evaluations were carried out from the 15th day of the experiment setup until 105 days. The characteristics evaluated were: first germination count (%), germination percentage (%), germination speed index, and average germination time (days). The fruits had an average biomass of 63.41 g, an average of 38 seeds per fruit, and fruit pulp with an average of 39.63 g. The germination of araticum seeds was not influenced by the accessions and fruit region.